2002
DOI: 10.1177/003288550208200204
|View full text |Cite
|
Sign up to set email alerts
|

Prisoner Perspectives on Inmate Culture in New Mexico and New Zealand: A Descriptive Case Study

Abstract: Medium security prisoners in two nations provided personal insights into the inmate social systems found in their facilities: Southern New Mexico Correctional Facility is located near New Mexico's border with Mexico; Christchurch Prison is in New Zealand's South Island. Besides personal biographical and sociolegal questions, the inmates in both facilities responded to a series of closed- and open-ended questions about inmate values and norms. The only modification was to cast them in terminology relevant to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…We suggest that this reflects the nature of the prison environment for many prisoners. Several commentators [21,27,28] have described a culture within prisons, characterized by values of selfreliance and the belief that emotional expression represents weakness. Changes toward detachment and away from emotion coping might reflect this.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that this reflects the nature of the prison environment for many prisoners. Several commentators [21,27,28] have described a culture within prisons, characterized by values of selfreliance and the belief that emotional expression represents weakness. Changes toward detachment and away from emotion coping might reflect this.…”
Section: Discussionmentioning
confidence: 99%
“…In order to get along with peers, inmates had to follow a code that acknowledged the utility of aggression, even violence, and discouraged prosocial associations with authority figures (Sykes and Messinger 1960, Irwin and Cressey 1962, Wellford 1967). The inmate code remains a topic of interest in recent research (see for example, Winfree et al 2002, Crewe 2005, Trammell 2009b); however, recent studies of modernday male prisons frequently focus on aggression and violence directly, not the code itself (see for example, Kerley et al 2005, Sorensen and Cunningham 2009, Turner and Ireland 2010. For example, Turner and Ireland (2010) examined the relationship between individual personality characteristics and bullying among incarcerated men.…”
Section: Literature Review Interpersonal Relationships Among Male Inmmentioning
confidence: 99%
“…Furthermore, for sex offenders gambling seems to be a way to fit in and to draw attention away from the classification of being a sex offender. The value of this function is likely to be substantial given that inmates, overall, have the least respect for sexual offenders (Winfree, Newbold, & Tubb, 2002), thus they may be more susceptible to victimization and violence from other offenders. From their study, O'Donnell and Edgar (1999) reported that most inmates (72 percent) agreed that sex offenders deserved to be bullied by other inmates.…”
Section: Socialization and Acceptance From Peersmentioning
confidence: 99%